Vegetable Salad Improves Lipid and Glucose Metabolism and Enhances Absorption of Specific Nutrients in Vegetables - Diah Mulyawati Utari; Indri Kartiko-Sari; Toshitaka Miyazaki; Hiroko Umezawa; Yumi Takeda; Mariko Oe; Wei Wang; Sumiko Kamoshita; Motomi Shibasaki; Ryosuke Matsuoka; Shigeru Yamamoto (Foods)
Vegetables are low in energy and rich in vitamins, minerals, and dietary fiber; various health benefits associated with their intake have been reported. Salads are one of the most convenient ways to consume vegetables and can be made simply by pouring mayonnaise, dressing, olive oil, or other condiments over a selection of vegetables. There are also many reports on the ways in which vegetable intake can improve health. However, there is no comprehensive review summarizing the health functions of vegetables when consumed as a salad. The effects of vegetable salads on amounts of vegetable intake, lifestyle-related diseases, and the absorption of specific nutrients through mayonnaise, as well as the effects of the order in which vegetable salad and carbohydrates are consumed, have been reported. In this review, the health functions of vegetable salad consumption are reported.